Letter to the Board of Supervisors from Robert A. Ain November, 1968 - Robert A. Ain:::::: (1968)
A letter to the board of supervisors from Robert A. Ain, the chairman for the Aviation Advisory Committee, advising that a proposed electrical power generating plant is a hazard to aviation and must restrict the height of said plant.